The role of massclusivity campaigns in consumer response and perceptions: the attitude toward luxury brands - Barata, Filipa Rodrigues Soares (2020)
The present dissertation purposes to understand the impact of the elaboration of Massclusivity campaigns, as a collaboration between a fast fashion brand and a luxury brand, on Brand Love and Brand Dilution of the Luxury Fashion Brand. To better understand the proposed topic, this research involves the analysis of the meaning and perception of the luxury concept with a focus on the fashion luxury market. This study focuses on the analyses of the traditional luxury brands adaptation to the digital era and how the mass customers perceptions of the luxury brands changed their dynamics to adapt into this globalized reality and how this adaptation altered the universal vision of what a luxury brand is. To better understand these topics, a survey questionnaire was conducted based on a proposed conceptual model. This model proposed that consumer response and perceptions towards a Massclusivity collaboration campaign will influence their attitude towards the ad and the brand. Consequently, to that understanding, customers will either create brand love or brand dilution for the luxury brand associated with the campaign. Results revealed that Massclusivity collaboration campaigns would create a significant positive impact on consumer perceptions and cognitive response consequently a positive relationship with the attitude towards the brand. Moreover, the attitude towards the brand showed a meaningful relationship with the construct brand love. The overall findings revealed that Massclusivity collaboration campaigns will have none to minimum impact on the Brand Dilution, on the other hand, the luxury brand will have a positive impact on customers Brand Love.